INTEGRATED MONITORING OF PHYTOPLANKTON IN A SHALLOW INLET OF PETER THE GREAT BAY (JAPAN SEA): DYNAMICS OF CHLOROPHYLL A AND NUTRIENTS - O. G. Shevchenko; K. O. Tevs; V. M. Shulkin (Известия ТИНРО, 2020)
Species composition and abundance of phytoplankton, chlorophyll a concentration and chemical parameters were monitored at the coast of Russky Island in the Paris Bay, the shallow secondary inlet of Peter the Great Bay in 2014–2015. In total, 103 species and intraspecific taxa of microalgae from 4 classes are identified. Dynamics of phytoplankton abundance did not coincide with the dynamics of chlorophyll a concentration. The abundance varied from 1.3 . 103 cells/L to 1.9 . 106 cells/L and chlorophyll a concentration changed in the range 0.21–6.08 mg/dm3 . Nutrients had the following concentrations: DSi 0.7–41.8 µM/L, DIN 0.0–7.1 µM/L, DIP 0.0–0.7 µM/L. Dynamics of microalgae density had no common seasonal pattern in 2014 and 2015, though seasonal dynamics of chlorophyll a, as well as variations of nutrients and other water properties were similar in both years.